A Companion to Early Modern Istanbul
1 online resource.
Keywords: This multi-disciplinary volume is the first collective effort to explore Istanbul, capital of the vast polyglot, multiethnic, and multireligious Ottoman empire and home to one of the world's largest and most diverse urban populations, as an early modern metropolis. It assembles topics seldom treated together and embraces novel subjects and fresh approaches to older debates. Contributors crisscross the socioeconomic, political, cultural, environmental, and spatial, to examine the myriad human and non-human actors, local and global, that shaped the city into one of the key sites of early modern urbanity. Contributors are: Oscar Aguirre-Mandujano , Zeynep Altok, Walter G. Andrews, Betül Başaran, Cem Behar, Maurits H. van den Boogert, John J. Curry, Linda T. Darling, Suraiya Faroqhi, Emine Fetvacı, Shirine Hamadeh, Cemal Kafadar, Çiğdem Kafescioğlu, Deniz Karakaş, Leyla Kayhan Elbirlik, B. Harun Küçük, Selim S. Kuru, Karen A. Leal, Gülru Necipoğlu, Christoph K. Neumann, Aslı Niyazioğlu, Amanda Phillips, Marinos Sariyannis, Aleksandar Shopov, Lucienne Thys-Şenocak, Nükhet Varlık, N. Zeynep Yelçe, Gülay Yılmaz, and Zeynep Yürekli.